Development and Implementation of an ESP32 Microcontroller and Monitoring System for Smart Door Lock Using RFID Sensor for E-KTP ID and Fingerprint Based on the Internet of Things - Attariq Ziad; Eva Darnila; Kurniawati (LPPM Universitas Malikussaleh, 2024)
This study aims to improve the effectiveness and efficiency of door security systems by integrating RFID technology, fingerprint recognition, and the Internet of Things (IoT). This system not only enables automatic locking but also provides real-time access control and monitoring through a web-based application. The technology supports high-level security through dual authentication methods, using E-ID cards and fingerprint sensors. Additionally, the implementation of IoT allows users to monitor and manage door access remotely, offering added flexibility and convenience. The system's trial shows high reliability in reading RFID and fingerprint data, with significant accuracy in various conditions. The results of this study contribute to the development of modern security solutions that can be applied in various environments, such as residential homes, offices, and public facilities, with the potential to reduce overall crime rates